The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1038/sj.leu.2402033
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors and translocations in lymphoid and myeloid leukemia

Abstract: Chromosomal translocations involving transcription factors and aberrant expression of transcription factors are frequently associated with leukemogenesis. Transcription factors are essential in maintaining the regulation of cell growth, development, and differentiation in the hematopoietic system. Alterations in the mechanisms that normally control these functions can lead to hematological malignancies. Further characterization of the molecular biology of leukemia will enhance our ability to develop disease-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 304 publications
0
41
0
Order By: Relevance
“…1,2 Transcription factors (TFs) play an important role in this process as they frequently show recurrent, somatically acquired, chromosomal abnormalities (translocations and inversions) and point mutations. 2,3 Familial cases of AML are best suited to define the initiating steps in leukemogenesis, and studies of familial AML have identified TF RUNX1 (AML1, CBFA2) as the first known familial leukemia susceptibility gene. 4,5 Core-binding factor CBFb is the cofactor of RUNX1, and both are essential for definitive hematopoiesis and are frequent fusion gene partners in chromosomal translocations in leukemia.…”
Section: To the Editormentioning
confidence: 99%
“…1,2 Transcription factors (TFs) play an important role in this process as they frequently show recurrent, somatically acquired, chromosomal abnormalities (translocations and inversions) and point mutations. 2,3 Familial cases of AML are best suited to define the initiating steps in leukemogenesis, and studies of familial AML have identified TF RUNX1 (AML1, CBFA2) as the first known familial leukemia susceptibility gene. 4,5 Core-binding factor CBFb is the cofactor of RUNX1, and both are essential for definitive hematopoiesis and are frequent fusion gene partners in chromosomal translocations in leukemia.…”
Section: To the Editormentioning
confidence: 99%
“…2,3 This can be appreciated by recognizing that the differentiation stop associated with acute myeloid leukemia in most cases involves translocations or other mutations that disturb the function of a transcription factor. 4,5 Further documentation comes from experiments involving ectopic expression of transcription factors in myeloid cell cultures 6,7 and targeted disruption of genes encoding transcription factors in mice. [8][9][10][11] Experimental evidence has shown that some transcription factors, such as CCAAT/enhancer binding protein ␣ (C/EBP-␣) and acute myeloid leukemia 1 (AML-1), 8,9 are important during early granulopoiesis whereas others, such as C/EBP-⑀ and CCAAT displacement protein (CDP), 10,12 first exert their function in more mature neutrophil precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Rsk ) or transcription factors [e.g., cyclic AMP-responsive element binding protein (CREB), Elk, and c-Myc] which enter the nucleus and regulate gene expression (19,20). NH 2 -terminal deleted forms of Raf and MEK1 proteins, which remove the Ras binding domain and the negative regulatory sites in CR1 and CR2 in Raf and the negative regulatory domain of MEK1, result in activated oncoproteins due to the aberrant stimulation of downstream kinases, transcription factors, and molecules involved in the prevention of apoptosis (17,18,21).…”
Section: Introductionmentioning
confidence: 99%